The Development of Assessment Rubric of Arabic Language Writing Based on National Qualifications Framework of Indonesia - Boeriswati, Endry; Mayuni, Ilza; Fahmi, Ari Khairurrijal; Surong, Kamal (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2023)
National qualifications framework of Indonesia needed to be technically elaborated and more operational (KKNI). Academic writing at the university level is difficult to measure without using a rubric. One form of this technique was the creation of an assessment rubric. This article aimed to develop an assessment instrument in the form of a rubric that focused on Arabic academic writing skills for undergraduate students based on the KKNI. The development research method was used with a convergent parallel mixed method model. The data were taken from three tertiary institutions consisting of 1 state university and 2 private universities. Data in the form of needs analysis results, expert analysis, and rubric reliability test results. The results of the trial were compared with the one group pre-test post-test experimental technique to prove that the rubric developed was feasible and reliable for use in teaching Arabic academic writing. The trial process proved that this rubric was feasible to use.  Based on the results of the T test, a result of 0.000 (p <0.05) was obtained. The results of the pretest and posttest experienced significant changes. It could be concluded that the Arabic academic writing rubric based on KKNI that was tested in the UHAMKA, UNJ, and UMSIDA. Arabic Education Study Programs was effective in Arabic academic writing tests. The result of the research was a rubric that can be used for Arabic academic writing in universities. This result was significant to be implemented especially for teachers and lecturers in Arabic writing fields.